2023
DOI: 10.1001/jamanetworkopen.2023.0429
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Maternal Mortality Missed by Vital Statistics in Hong Kong, 2000-2019

Abstract: ImportanceReducing maternal mortality is a global objective. The maternal mortality ratio (MMR) is low in Hong Kong, China, but there has been no local confidential enquiry into maternal death, and underreporting is likely.ObjectiveTo determine the causes and timing of maternal death in Hong Kong and identify deaths and their causes that were missed by the Hong Kong vital statistics database.Design, Setting, and ParticipantsThis cross-sectional study was conducted among all 8 public maternity hospitals in Hong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The low MMR is multifactorial and related to the provision of good obstetric, medical, and surgical care, as well as good health conditions of pregnant women 6,8 . Hong Kong has an efficient transportation network, a universal lowcost healthcare system, free comprehensive high-quality antenatal and intrapartum care and emergency obstetric services 9,10 .…”
Section: Trend and Causes Of Maternal Mortality In Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation
“…The low MMR is multifactorial and related to the provision of good obstetric, medical, and surgical care, as well as good health conditions of pregnant women 6,8 . Hong Kong has an efficient transportation network, a universal lowcost healthcare system, free comprehensive high-quality antenatal and intrapartum care and emergency obstetric services 9,10 .…”
Section: Trend and Causes Of Maternal Mortality In Hong Kongmentioning
confidence: 99%
“…In a cross-sectional study on maternal death events from 2000 to 2019 in Hong Kong, the leading direct causes were suicide, hypertensive disorders, and obstetric haemorrhage, followed by amniotic fluid embolism, pregnancy-related infection, pulmonary embolism, and cardiac diseases, whereas the leading indirect causes were stroke and cancer, followed by infection (including hepatitis B) and cardiac diseases 9 . Deaths related to abortion or ectopic pregnancy have become uncommon 9,10 .…”
Section: Trend and Causes Of Maternal Mortality In Hong Kongmentioning
confidence: 99%
“…A study in Hong Kong found that the database failed to capture 90.5% of maternal deaths from public health hospitals (Cheung et al, 2023). Another study in Banten found that the odds of a maternal death during delivery being missed was 70% less than a maternal death during pregnancy being missed.…”
Section: Maternal Mortality In Jember Regencymentioning
confidence: 99%
“…However, the number of maternal mortalities may be under-reported due to the lack of a confidential enquiry system to record maternal-nearmiss morbidities. Between 2000 and 2019, suicide and hypertensive disorders were the leading causes of maternal death in Hong Kong 2 .…”
Section: Introductionmentioning
confidence: 99%